Intraoperative digital breast tomosynthesis using a dedicated device is more accurate than standard intraoperative mammography for identifying positive margins. Issue 12 (December 2019) - Garlaschi, A.; Fregatti, P.; Oddone, C.; Friedman, D.; Houssami, N.; Calabrese, M.; Tagliafico, A.S.
Abstract : AIM: To compare a standard intra-operative mammography (IM) device with digital breast tomosynthesis using a dedicated device (Mozart system) in the evaluation of surgical margins at first excision. MATERIALS AND METHODS: The study received institutional review board approval and written informed consent was obtained from participants. From January 2018 to December 2018, a prospective analysis of the images of IM device and intra-operative digital breast tomosynthesis with a dedicated device (Mozart system) in n= 89 breast cancer patients (average patients age: 58 years, age range: 35–76 years) was undertaken. Images were evaluated by two expert breast radiologists independently of each other and blinded to each other's interpretation, who indicated the positive cases requiring surgical re-excision intra-operatively. RESULTS: Mean cancer size was 12.5±4.5 mm. Radiological signs of the lesions were microcalcifications ( n= 71), nodules ( n= 10), and architectural distortions ( n= 8). A total of 20/89 (17%) patients underwent intra-operative re-excision for positive margins. Intra-operative digital breast tomosynthesis with a dedicated device and IM showed discrepancies in 15/89 cases (17%). Mozart system results informed the necessity to perform a re-excision ( n= 15). Overall, receiver operating characteristic (ROC) curve analysis showed and area under the ROC curve (AUC) of 0.82 for the Mozart system versus 0.65 for IM. ROC analysis of radiological findings with microcalcifications showed an AUC of 0.92 for the Mozart system versus 0.74 for IM, whereas AUC in cases with no microcalcifications were 0.87 and 0.75, respectively. CONCLUSION: Intra-operative digital breast tomosynthesis with a dedicated device provides more information (better accuracy) than IM and facilitated a reduction in re-excision rates. Highlights: Intraoperative digital breast tomosynthesis and intraoperative mammography (IM) had discrepancies in 15/89 cases (17%). AUC was 0.82 for the Mozart system versus 0.65 for IM. Microcalcifications showed an AUC of 0.92 for the Mozart system versus 0.74 of IM. In cases with no microcalcifications AUC was 0.87 for tomosynthesis and 0.75 for IM.